Transparent conductive film and crystalline transparent conductive film

A transparent conductive film with Hf and Sn regions on a cycloolefin substrate achieves efficient crystallization and conductivity by overcoming the limitations of cycloolefin films' low heat resistance, improving productivity and performance.

CN111383794BActive Publication Date: 2024-12-13NITTO DENKO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201911374409.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-28
Filing Date
2019-12-27
Publication Date
2024-12-13
Estimated Expiration
2039-12-27

AI Technical Summary

Technical Problem

Cycloolefin films used in transparent conductive films cannot be heat-treated at high temperatures due to their low heat resistance and low glass transition point, leading to poor productivity and conductivity.

Method used

A transparent conductive film with a structure comprising a transparent substrate, an amorphous transparent conductive layer containing Hf and Sn regions, which allows for crystallization at low temperatures, enhancing conductivity and productivity.

Benefits of technology

The film achieves good crystallization rates and excellent conductivity while maintaining productivity by using a Hf and Sn region structure, allowing for efficient crystallization at low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111383794B_ABST
    Figure CN111383794B_ABST
Patent Text Reader

Abstract

The present invention relates to a transparent conductive film and a crystalline transparent conductive film. The transparent conductive film (1) comprises: a transparent substrate (2) and a transparent conductive layer (5) arranged on the upper side of the transparent substrate (2), wherein the transparent conductive layer (5) is amorphous and has: an Hf region (8) formed of an indium oxide containing hafnium and an Sn region (6) formed of an indium oxide containing tin in the thickness direction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a transparent conductive film and a crystalline transparent conductive film, and more particularly to a transparent conductive film and a crystalline transparent conductive film suitable for optical applications. Background Art

[0002] Transparent conductive films having a transparent conductive layer including indium tin oxide (ITO) formed in a desired electrode pattern have been used for optical applications such as touch panels. In addition, in recent years, electromagnetic waves generated by current flowing through the touch panel may affect image display devices such as OLED and LCD, so in order to shield the electromagnetic waves, it has been proposed to configure a non-patterned transparent conductive film between the touch panel and the image display device.

[0003] As a transparent conductive film, for example, Patent Document 1 discloses a transparent conductive film including a transparent resin film, a hard coat layer, an intermediate layer having a refractive index of 1.65 to 1.90, and a transparent conductive layer in this order.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-62609 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] Generally, a transparent conductive film including ITO is heated to crystallize the ITO, thereby improving the conductivity (low resistance).

[0009] On the other hand, as a transparent resin film, cycloolefin films are sometimes used from the viewpoint of having various functions such as transparency and polarization. However, such cycloolefin films cannot be heat-treated at high temperatures due to their low glass transition point and low heat resistance. In addition, if heated at low temperatures, the heating time becomes long, resulting in poor productivity.

[0010] The present invention provides a transparent conductive film having a good crystallization rate at low temperature and excellent conductivity.

[0011] Solutions for solving problems

[0012] The present invention [1] comprises a transparent conductive film comprising: a transparent substrate and a transparent conductive layer arranged on one side of the transparent substrate in the thickness direction, wherein the transparent conductive layer is amorphous and has, in the thickness direction, an Hf region formed of an indium oxide containing hafnium and a Sn region formed of an indium oxide containing tin.

[0013] The present invention [2] comprises the transparent conductive film according to [1], wherein the Hf region is arranged on one side in the thickness direction of the Sn region.

[0014] The present invention [3] comprises the transparent conductive film according to [1] or [2], wherein the transparent conductive layer has a thickness of 10 nm to 35 nm.

[0015] The present invention [4] comprises the transparent conductive film according to any one of [1] to [3], wherein the transparent substrate is a cycloolefin-based film.

[0016] The present invention [5] includes a crystalline transparent conductive film obtained by crystallizing the transparent conductive layer of the transparent conductive film according to any one of [1] to [4].

[0017] Effects of the Invention

[0018] According to the transparent conductive film of the present invention, it comprises a transparent substrate and a transparent conductive layer, and the transparent conductive layer has an Hf region formed of an indium oxide containing hafnium and an Sn region formed of an indium oxide containing tin in the thickness direction. Therefore, the crystallization rate at low temperature is good and the conductivity is excellent.

[0019] Furthermore, the crystalline transparent conductive film of the present invention has good productivity and excellent conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A cross-sectional view showing a first embodiment of the transparent conductive film of the present invention.

[0021] Figure 2 Show that Figure 1 The transparent conductive film shown is a crystalline transparent conductive film obtained by crystallizing the transparent conductive film.

[0022] Figure 3 A modified example (a form not having a Sn / Hf mixed region) of the first embodiment of the transparent conductive film of the present invention is shown.

[0023] Figure 4 A cross-sectional view showing a second embodiment of the transparent conductive film of the present invention.

[0024] Figure 5 A cross-sectional view showing a third embodiment of the transparent conductive film of the present invention.

[0025] Figure 6 The graph obtained by measuring the transparent conductive layer of the transparent conductive film of Example 1 by X-ray photoelectron spectroscopy is shown.

[0026] Figure 7 The graphs obtained by measuring the crystallization rate for each Example and each Comparative Example are shown.

[0027] Description of Reference Numerals

[0028] 1 Transparent conductive film

[0029] 1A Crystalline transparent conductive film

[0030] 2 Transparent substrate

[0031] 5. Transparent Conductive Layer

[0032] 5A Crystalline transparent conductive layer

[0033] 6 Sn region

[0034] 7 Sn / Hf mixed region

[0035] 8 Hf region DETAILED DESCRIPTION

[0036] <First Embodiment>

[0037] Reference Figure 1 , one embodiment of the first embodiment of the transparent conductive film of the present invention is described.

[0038] Figure 1 In the figure, the up-down direction on the paper is the up-down direction (thickness direction, first direction), the upper side on the paper is the upper side (one side in the thickness direction, one side in the first direction), and the lower side on the paper is the lower side (the other side in the thickness direction, the other side in the first direction). In addition, the left-right direction and the depth direction on the paper are the plane directions orthogonal to the up-down direction. Specifically, the direction arrows in each figure shall prevail.

[0039] 1. Transparent conductive film

[0040] The transparent conductive film 1 is in the shape of a film (including a sheet shape) having a predetermined thickness, extending in a predetermined direction (surface direction) orthogonal to the thickness direction, and having a flat upper surface and a flat lower surface. The transparent conductive film 1 is, for example, a component of a touch panel substrate, an electromagnetic wave shielding body, etc., which is provided by an image display device, that is, it is not an image display device. That is, the transparent conductive film 1 is a component for manufacturing an image display device, etc., and is an industrially usable device that does not include an image display element such as an OLED module, but includes a transparent substrate 2, a hard coating layer 3, an optical adjustment layer 4, and a transparent conductive layer 5, and is circulated as a component itself.

[0041] Specifically, if Figure 1As shown, the transparent conductive film 1 includes: a transparent substrate 2, a hard coating layer 3 arranged on the upper surface (one surface in the thickness direction) of the transparent substrate 2, an optical adjustment layer 4 arranged on the upper surface of the hard coating layer 3, and a transparent conductive layer 5 arranged on the upper surface of the optical adjustment layer 4.

[0042] More specifically, the transparent conductive film 1 includes a transparent substrate 2, a hard coat layer 3, an optical adjustment layer 4, and a transparent conductive layer 5 in this order. The transparent conductive film 1 is preferably formed of the transparent substrate 2, the hard coat layer 3, the optical adjustment layer 4, and the transparent conductive layer 5.

[0043] 2. Transparent substrate

[0044] The transparent substrate 2 is a transparent substrate for ensuring the mechanical strength of the transparent conductive film 1. That is, the transparent substrate 2 supports the transparent conductive layer 5 together with the hard coat layer 3 and the optical adjustment layer 4.

[0045] The transparent substrate 2 is the lowermost layer of the transparent conductive film 1 and has a film shape. The transparent substrate 2 is disposed on the entire lower surface of the hard coating layer 3 so as to be in contact with the lower surface of the hard coating layer 3 .

[0046] The transparent substrate 2 is, for example, a transparent polymer film. Examples of the material of the transparent substrate 2 include olefin resins such as polyethylene, polypropylene, and cycloolefin polymers, polyester resins such as polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate, (meth) acrylic resins such as polymethacrylate (acrylic resins and / or methacrylic resins), polycarbonate resins, polyethersulfone resins, polyarylate resins, melamine resins, polyamide resins, polyimide resins, cellulose resins, and polystyrene resins. The transparent substrate 2 may be used alone or in combination of two or more.

[0047] Preferably, a non-crystalline thermoplastic resin is used, which can provide a desired polarization axis and has excellent transparency.

[0048] As such a non-crystalline thermoplastic resin, preferably, a cycloolefin polymer is mentioned. That is, the transparent substrate 2 is preferably a cycloolefin-based film formed of a cycloolefin polymer.

[0049] The cycloolefin polymer is a polymer obtained by polymerizing a cycloolefin monomer and having an alicyclic structure in a repeating unit of the main chain. The cycloolefin resin is preferably an amorphous cycloolefin resin.

[0050] Examples of the cycloolefin polymer include a cycloolefin homopolymer formed from a cycloolefin monomer and a cycloolefin copolymer formed from a copolymer of a cycloolefin monomer and an olefin such as ethylene.

[0051] As the cycloolefin monomer, polycyclic olefins such as norbornene, methyl norbornene, dimethyl norbornene, ethylidene norbornene, butyl norbornene, dicyclopentadiene, dihydrodicyclopentadiene, tetracyclododecene, tricyclopentadiene, and monocyclic olefins such as cyclobutene, cyclopentene, cyclooctadiene, and cyclooctatriene can be cited. Preferably, polycyclic olefins can be cited. These cycloolefins can be used alone or in combination of two or more.

[0052] The glass transition point (Tg) of the transparent base material 2 is, for example, 150° C. or lower, preferably 120° C. or lower, and for example, 50° C. or higher, preferably 70° C. or higher.

[0053] The transparent substrate 2 preferably has a polarization axis in the plane direction. Thus, when visually observing an image display device having the transparent conductive film 1 through polarized glasses (sunglasses, etc.), the image display device can be identified by suppressing the orthogonal Nicol prism caused by the polarized glasses and the polarizer in the image display device.

[0054] The total light transmittance (JIS K 7375-2008) of the transparent base material 2 is, for example, 80% or more, or preferably 85% or more.

[0055] The thickness of the transparent substrate 2 is, for example, 2 μm or more, preferably 20 μm or more, and, for example, 300 μm or less, preferably 150 μm or less, from the viewpoint of mechanical strength. The thickness of the transparent substrate 2 can be measured using, for example, a microgauge thickness meter.

[0056] 4. Hard coating

[0057] The hard coat layer 3 is a protective layer for preventing the transparent substrate 2 from being damaged when the transparent conductive film 1 is produced, and is also a scratch-resistant layer for preventing the transparent conductive layer 5 from being scratched when a plurality of transparent conductive films 1 are stacked.

[0058] The hard coating layer 3 has a thin film shape. The hard coating layer 3 is disposed on the entire upper surface of the transparent substrate 2 in a manner in contact with the upper surface of the transparent substrate 2. More specifically, the hard coating layer 3 is disposed between the transparent substrate 2 and the optical adjustment layer 4 in a manner in contact with the upper surface of the transparent substrate 2 and the lower surface of the optical adjustment layer 4.

[0059] The hard coating layer 3 is formed of a hard coating composition. The hard coating composition contains a resin.

[0060] Examples of the resin include curable resins and thermoplastic resins (for example, polyolefin resins), and preferably, curable resins are used.

[0061] Examples of the curable resin include active energy ray-curable resins that are cured by irradiation with active energy rays (specifically, ultraviolet rays, electron beams, etc.), and thermosetting resins that are cured by heating, and preferably active energy ray-curable resins are used.

[0062] Examples of the active energy ray-curable resin include polymers containing a functional group having a polymerizable carbon-carbon double bond in the molecule. Examples of such functional groups include vinyl groups, (meth)acryloyl groups (methacryloyl groups and / or acryloyl groups), and the like.

[0063] Specific examples of the active energy ray-curable resin include (meth)acrylic ultraviolet-curable resins such as urethane acrylate and epoxy acrylate.

[0064] Examples of curable resins other than active energy ray-curable resins include urethane resins, melamine resins, alkyd resins, siloxane-based polymers, and organosilane condensates.

[0065] These resins can be used alone or in combination of two or more.

[0066] The hard coating composition may also contain particles. Thus, the hard coating layer 3 can be made into an anti-blocking layer having anti-blocking properties.

[0067] Examples of the particles include organic particles and inorganic particles. Examples of organic particles include cross-linked acrylic particles such as cross-linked acrylic styrene resin particles. Examples of inorganic particles include silica particles, metal oxide particles such as zirconium oxide, titanium oxide, zinc oxide, tin oxide, and carbonate particles such as calcium carbonate. The particles may be used alone or in combination of two or more.

[0068] The hard coating composition may further contain known additives such as a leveling agent, a thixotropic agent, and an antistatic agent.

[0069] The thickness of the hard coating layer 3 is, for example, 0.1 μm or more, preferably 0.5 μm or more, and, for example, 10 μm or less, preferably 3 μm or less, from the viewpoint of scratch resistance. The thickness of the hard coating layer 3 can be calculated based on the wavelength of the interference spectrum observed using a transient multi-channel photometry system (e.g., "MCPD 2000" manufactured by Otsuka Electronics Co., Ltd.).

[0070] 4. Optical Adjustment Layer

[0071] The optical adjustment layer 4 is a layer for adjusting the optical properties (eg, refractive index) of the transparent conductive film 1 in order to suppress pattern recognition of the transparent conductive layer 5 or suppress reflection at the interface in the transparent conductive film 1 and ensure excellent transparency of the transparent conductive film 1 .

[0072] The optical adjustment layer 4 has a thin film shape and is disposed on the entire upper surface of the hard coating layer 3 so as to be in contact with the upper surface of the hard coating layer 3. More specifically, the optical adjustment layer 4 is disposed between the hard coating layer 3 and the transparent conductive layer 5 so as to be in contact with the upper surface of the hard coating layer 3 and the lower surface of the transparent conductive layer 5.

[0073] The optical adjustment layer 4 is formed of an optical adjustment composition. The optical adjustment composition contains a resin, preferably a resin and particles. That is, the optical adjustment layer 4 is preferably a resin layer containing particles.

[0074] Examples of the resin include the resins exemplified in the hard coating composition, preferably a curable resin, more preferably an active energy ray-curable resin, and still more preferably a (meth)acrylic ultraviolet curable resin.

[0075] The content ratio of the resin relative to the optical adjustment composition is, for example, 10 mass % or more, preferably 25 mass % or more, and, for example, 95 mass % or less, preferably 60 mass % or less.

[0076] As particles, appropriate materials can be selected according to the refractive index required for the optical adjustment layer, and for example, the particles exemplified in the hard coating composition can be listed. From the viewpoint of refractive index, inorganic particles can be preferably listed, metal oxide particles can be more preferably listed, and zirconium oxide particles (ZrO2) can be further preferably listed.

[0077] The content ratio of the particles relative to the optical adjustment composition is, for example, 5 mass % or more, preferably 40 mass % or more, and, for example, 90 mass % or less, preferably 75 mass % or less.

[0078] The optical adjustment composition may further contain known additives such as a leveling agent, a thixotropic agent, and an antistatic agent.

[0079] The refractive index of the optical adjustment layer 4 is, for example, 1.40 or more, preferably 1.55 or more, and, for example, 1.80 or less, preferably 1.70 or less. The refractive index can be measured using, for example, an Abbe refractometer.

[0080] The thickness of the optical adjustment layer 4 is, for example, 5 nm or more, preferably 10 nm or more, and, for example, 200 nm or less, preferably 100 nm or less. The thickness of the optical adjustment layer 4 can be calculated based on the wavelength of the interference spectrum observed using a transient multi-channel photometry system.

[0081] 5. Transparent conductive layer

[0082] The transparent conductive layer 5 is a transparent layer that is crystallized as necessary to exhibit excellent conductivity.

[0083] The transparent conductive layer 5 is the uppermost layer of the transparent conductive film 1 and has a thin film shape. The transparent conductive layer 5 is disposed on the entire upper surface of the optical adjustment layer 4 so as to be in contact with the upper surface of the optical adjustment layer 4 .

[0084] The transparent conductive layer 5 includes a Sn region 6 , a Sn / Hf mixed region 7 , and a Hf region 8 in this order from the bottom.

[0085] The Sn region 6 is a lower layer formed so as to extend in the surface direction on the upper surface of the optical adjustment layer 4. The Sn region 6 is formed of an indium-based oxide containing tin (Sn), and is preferably formed of indium tin composite oxide (ITO).

[0086] In the Sn region 6, the content of tin oxide (SnO2) relative to the total amount of tin oxide and indium oxide (In2O3) is, for example, 0.5 mass% or more, preferably 3 mass% or more, and, for example, 15 mass% or less, preferably 13 mass% or less. When the content of tin oxide is above the lower limit, the crystallization rate of the transparent conductive layer 5 can be improved. When the content of tin oxide is below the upper limit, the conductivity of the transparent conductive layer 5 can be improved.

[0087] The Sn region 6 may contain inevitable impurities as metals other than Sn and In.

[0088] In addition, the Sn region 6 does not substantially contain Hf. That is, in the Sn region 6, no Hf element is detected in the measurement by X-ray photoelectron spectroscopy.

[0089] The thickness of the Sn region 6 is, for example, 1 nm or more, preferably 3 nm or more, preferably 10 nm or more, and, for example, 50 nm or less, preferably 40 nm or less, and more preferably 30 nm or less. The thickness of each region can be determined by measuring the transparent conductive layer 5 along the thickness direction using X-ray photoelectron spectroscopy.

[0090] The Sn / Hf mixed region 7 is an intermediate layer formed on the upper side of the Sn region 6 in a manner extending in the surface direction. The Sn / Hf mixed region 7 contains both the elements contained in the Sn region 6 and the elements contained in the Hf region 8. Specifically, it is formed of an oxide containing Sn, Hf, and In. In addition, the Sn / Hf mixed region 7 may contain Ta (tantalum), in which case it is formed of an oxide containing Sn, Hf, Ta, and In.

[0091] Preferably, the Sn / Hf mixed region 7 is a region that gradually changes from the Sn region 6 to the Hf region 8. That is, as the content ratio of the Sn element gradually decreases from the lower end to the upper end of the Sn / Hf mixed region 7, the content ratio of the Hf gradually increases. In other words, there is no interface in the cross section within the transparent conductive layer 5. That is, the transparent conductive layer 5 does not have both the Sn region-Sn / Hf mixed region interface (6 / 7 interface) and the Sn / Hf mixed region-Hf region interface (7 / 8 interface).

[0092] The thickness of the Sn / Hf mixed region 7 is, for example, not less than 1 nm, preferably not less than 2 nm, more preferably not less than 3 nm, and, for example, not more than 10 nm, preferably not more than 8 nm, more preferably not more than 6 nm.

[0093] The Hf region 8 is an upper layer formed to extend in the surface direction on the upper side of the Sn / Hf mixed region 7. The Hf region 8 is formed of an indium-based oxide containing hafnium (Hf), preferably an oxide containing Hf, Ta (tantalum), and In.

[0094] The content ratio (atomic ratio) of Hf, when no Ta is included, is, in terms of Hf / (Hf+In), for example, 0.2 at % or more, preferably 0.5 at % or more, and for example, 3.0 at % or less, preferably 2.5 at % or less.

[0095] On the other hand, the content ratio (atomic ratio) of Hf, when Ta is included, is calculated as Hf / (Hf+Ta+In), for example, 0.2 at % or more, preferably 0.5 at % or more, and for example, 3.0 at % or less, preferably 2.5 at % or less.

[0096] The content ratio (atomic ratio) of Ta is, for example, 0.02 at % or more, preferably 0.1 at % or more, and for example, 1.3 at % or less, preferably 1.0 at % or less, in terms of Ta / (Hf+Ta+In).

[0097] The In content ratio (atomic ratio) is, for example, 95.0 at % or more, preferably 97.0 at % or more, and for example, 99.7 at % or less, preferably 99.0 at % or less, in terms of In / (Hf+In) or In / (Hf+Ta+In).

[0098] The Hf region 8 may contain inevitable impurities as metals other than Hf, Ta, and In.

[0099] In addition, the Hf region 8 does not substantially contain Sn. That is, in the Hf region 8, no Sn element is detected in the measurement by X-ray photoelectron spectroscopy.

[0100] The thickness of the Hf region 8 is, for example, not less than 1 nm, preferably not less than 3 nm, and preferably not less than 8 nm, and is, for example, not more than 50 nm, preferably not more than 40 nm, and more preferably not more than 30 nm.

[0101] The thickness of the Hf region 8 is preferably greater than the thickness of the Sn region 6. This allows for a more excellent crystallization rate at a low temperature.

[0102] The surface resistivity of the upper surface of the transparent conductive layer 5 is, for example, 100 Ω / □ or less, preferably 80 Ω / □ or less, and, for example, 10 Ω / □ or more. The surface resistivity can be measured by a four-probe method.

[0103] The resistivity of the upper surface of the transparent conductive layer 5 is, for example, 3.0×10 -4 Ω·cm or less, preferably 2.5×10 -4 Ω·cm or less, and for example, 1.0×10 -4 Ω·cm or more. The resistivity can be measured by the four-terminal method.

[0104] The thickness of the transparent conductive layer 5 as a whole is, for example, 5 nm or more, preferably 10 nm or more, and, for example, 80 nm or less, preferably 35 nm or less. By setting the thickness of the transparent conductive layer 5 to the above range, it is possible to more reliably achieve a balance between the crystallization rate at a low temperature and the conductivity. The thickness of the transparent conductive layer 5 as a whole can be measured, for example, by observing the cross section of the transparent conductive film 1 using a transmission electron microscope.

[0105] The transparent conductive layer 5 is amorphous. The amorphous nature of the transparent conductive layer 5 can be determined, for example, by immersing the transparent conductive film 1 in hydrochloric acid (20° C., concentration 5 mass%) for 15 minutes, then washing with water and drying, and then measuring the terminal resistance of about 15 mm on the surface of the transparent conductive layer 5 side. For the transparent conductive film 1 after the above immersion, washing with water, and drying, if the terminal resistance of 15 mm exceeds 10 kΩ, the transparent conductive layer 5 is amorphous, and if the above resistance is less than 10 kΩ, the transparent conductive layer is crystalline.

[0106] 6. Method for manufacturing transparent conductive film

[0107] The method for producing the transparent conductive film 1 is described below. To produce the transparent conductive film 1, for example, a hard coat layer 3, an optical adjustment layer 4, and a transparent conductive layer 5 are sequentially provided on the upper surface of a transparent substrate 2. This is described in detail below.

[0108] First, a known or commercially available transparent substrate 2 is prepared. Preferably, a cycloolefin-based film is prepared.

[0109] Then, as required, from the viewpoint of the adhesion between the transparent substrate 2 and the hard coat layer 3, etching treatments such as sputtering, corona discharge, flame, ultraviolet irradiation, electron beam irradiation, chemical conversion, oxidation, and the like, and primer treatments may be applied to the upper surface of the transparent substrate 2. In addition, the transparent substrate 2 may be dusted and cleaned by solvent cleaning, ultrasonic cleaning, and the like.

[0110] Next, the hard coating layer 3 is provided on the upper surface of the transparent substrate 2. For example, the hard coating layer 3 is formed on the upper surface of the transparent substrate 2 by wet coating the hard coating composition on the upper surface of the transparent substrate 2.

[0111] Specifically, for example, a solution (varnish) obtained by diluting the hard coating composition with a solvent is prepared, and then the hard coating composition solution is applied to the upper surface of the transparent substrate 2 and dried.

[0112] As the solvent, for example, an organic solvent, an aqueous solvent (specifically, water) etc. can be listed, and preferably an organic solvent can be listed. As the organic solvent, for example, alcohol compounds such as methanol, ethanol, and isopropanol, ketone compounds such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, ester compounds such as ethyl acetate and butyl acetate, ether compounds such as propylene glycol monomethyl ether, and aromatic compounds such as toluene and xylene can be listed. These solvents can be used alone or in combination of two or more.

[0113] The solid content concentration in the hard coating composition solution is, for example, 1 mass % or more, preferably 10 mass % or more, and, for example, 30 mass % or less, preferably 20 mass % or less.

[0114] The coating method can be appropriately selected according to the hard coating composition solution and the transparent substrate 2. Examples of the coating method include dip coating, air knife coating, curtain coating, roll coating, wire bar coating, gravure coating, and extrusion coating.

[0115] The drying temperature is, for example, 50° C. or higher, preferably 70° C. or higher, and for example, 150° C. or lower, preferably 100° C. or lower.

[0116] The drying time is, for example, 0.5 minute or more, preferably 1 minute or more, and for example, 60 minutes or less, preferably 20 minutes or less.

[0117] Next, when the hard coating composition contains an active energy ray-curable resin, after the hard coating composition solution is dried, the active energy ray-curable resin is cured by irradiating the hard coating composition solution with active energy rays.

[0118] In addition, when the hard coating composition contains a thermosetting resin, the thermosetting resin can be thermally cured together with the drying of the solvent by this drying step.

[0119] Next, the optical adjustment layer 4 is provided on the upper surface of the hard coat layer 3. For example, the optical adjustment layer 4 is formed on the upper surface of the hard coat layer 3 by wet-coating an optical adjustment composition on the upper surface of the hard coat layer 3.

[0120] Specifically, for example, a solution (varnish) obtained by diluting the optical adjustment composition with a solvent is prepared, and then the optical adjustment composition solution is applied to the upper surface of the hard coat layer 3 and dried.

[0121] The conditions for preparation, coating, drying, etc. of the optical adjustment composition may be the same as those exemplified for the preparation, coating, drying, etc. of the hard coating composition.

[0122] When the optical adjustment composition contains an active energy ray-curable resin, the active energy ray-curable resin is cured by irradiating the optical adjustment composition solution with active energy rays after drying.

[0123] In addition, when the optical adjustment composition contains a thermosetting resin, the thermosetting resin can be thermally cured together with the drying of the solvent by this drying step.

[0124] Next, the transparent conductive layer 5 is provided on the upper surface of the optical adjustment layer 4. For example, the transparent conductive layer 5 is formed on the upper surface of the optical adjustment layer 4 by a dry method.

[0125] In forming the transparent conductive layer 5, the Sn region 6 and the Hf region 8 are sequentially formed. It is preferable to continuously form the Sn region 6 and the Hf region 8 by the same dry method. Thus, at the interface between the Sn region 6 and the Hf region 8, the components are mixed with each other, thereby forming the Sn / Hf mixed region 7.

[0126] Examples of the dry method include vacuum deposition, sputtering, and ion plating. Preferably, sputtering is used. The desired transparent conductive layer 5 can be formed by this method.

[0127] Examples of the sputtering method include a dipole sputtering method, an ECR (electron cyclotron resonance) sputtering method, a magnetron sputtering method, and an ion beam sputtering method. Preferably, the magnetron sputtering method is used.

[0128] As a target material for forming the Sn region 6, an indium-based oxide containing Sn can be mentioned. Preferably, ITO (oxide containing In—Sn) is mentioned.

[0129] In the formation of the Sn region 6, as the sputtering gas, for example, an inert gas such as Ar can be cited. In addition, a reactive gas such as oxygen can be used in combination as needed. When the reactive gas is used in combination, the flow rate ratio of the reactive gas relative to the total flow rate ratio of the sputtering gas and the reactive gas is, for example, 0.1 flow % or more and 5 flow % or less.

[0130] The sputtering method is performed in a vacuum. Specifically, the gas pressure during sputtering is, for example, 1 Pa or less, preferably 0.7 Pa or less, from the viewpoint of suppressing a decrease in the sputtering rate and maintaining discharge stability.

[0131] The power source used in the sputtering method may be, for example, any of a DC power source, an AC power source, an MF power source, and an RF power source, or a combination thereof.

[0132] The set thickness (target value) of the sputtering device is, for example, 5 nm or more, preferably 10 nm or more, more preferably 12 nm or more, and, for example, 50 nm or less, preferably 30 nm or less, and DC is more preferably 20 nm or less.

[0133] In the formation of the Hf region 8, as a target material, an indium oxide containing Hf can be cited. Preferably, an oxide containing In, Hf and Ta (an oxide containing In-Hf-Ta) can be cited. As a specific example of such a target, for example, an oxide sintered body described in Japanese Patent Application Publication No. 10-269843, Japanese Patent Application Publication No. 2017-149636, Japanese Patent Application Publication No. 2018-188677, etc. can be cited.

[0134] The set thickness of the sputtering device is, for example, 5 nm or more, preferably 10 nm or more, more preferably 15 nm or more, and, for example, 50 nm or less, preferably 30 nm or less, more preferably 25 nm or less.

[0135] In forming the Hf region 8 , the conditions of the sputtering method can be the same as those for forming the Sn region 6 except for the above.

[0136] In order to form the transparent conductive layer 5 having a desired thickness, sputtering may be performed a plurality of times by appropriately setting the target material, sputtering conditions, and the like.

[0137] In the above-mentioned manufacturing method, the hard coating layer 3, the optical adjustment layer 4 and the transparent conductive layer 5 can be formed on the transparent substrate 2 while the transparent substrate 2 is conveyed in a roll-to-roll manner, and a part or all of these layers can also be formed in a batch manner (single-sheet manner).

[0138] From the viewpoint of productivity, it is preferred to form each layer on the transparent substrate 2 by a roll-to-roll method while conveying the transparent substrate 2 .

[0139] In this way, Figure 1 As shown, a transparent conductive film 1 (amorphous transparent conductive film) is obtained which sequentially comprises a transparent substrate 2, a hard coat layer 3, an optical adjustment layer 4 and a transparent conductive layer 5. The transparent conductive layer 5 is amorphous and sequentially comprises a Sn region 6, a Sn / Hf mixed region 7 and a Hf region 8 from the bottom.

[0140] The thickness of the obtained transparent conductive film 1 is, for example, 2 μm or more, preferably 20 μm or more, and, for example, 100 μm or less, preferably 50 μm or less.

[0141] In addition, in the transparent conductive film 1, the transparent conductive layer 5 has the Hf region 8 and the Sn region 6 in the thickness direction, so that it is possible to achieve a balance between excellent crystallization speed and conductivity. That is, the transparent conductive layer 5 can be crystallized in a short time at a low temperature, and the crystallized transparent conductive film 1 (crystalline transparent conductive film 1A, see Figure 2 ) exhibits excellent electrical conductivity.

[0142] 7. Crystalline transparent conductive film

[0143] A method for producing the crystalline transparent conductive film 1A will be described. In order to produce the crystalline transparent conductive film 1A, the transparent conductive film 1 is heated.

[0144] Specifically, the transparent conductive film 1 is heated in the atmosphere.

[0145] The heating can be performed using, for example, an infrared heater, an oven, or the like.

[0146] The heating temperature is, for example, 80° C. or higher, preferably 90° C. or higher, and, for example, 150° C. or lower, preferably 120° C. or lower, and more preferably 100° C. or lower. When the heating temperature is above the lower limit, the transparent conductive layer 5 can be reliably crystallized, and the crystalline transparent conductive layer 5A can be reliably obtained. On the other hand, when the heating temperature is below the upper limit, thermal damage to the transparent substrate 2 can be suppressed.

[0147] The heating time is, for example, 1 minute or more, preferably 10 minutes or more, and, for example, 60 minutes or less, preferably 30 minutes or less. When the heating time is above the lower limit, the transparent conductive layer 5 can be reliably crystallized. On the other hand, when the heating temperature is below the upper limit, the production efficiency of the crystalline transparent conductive film 1A is excellent.

[0148] As a result, the transparent conductive layer 5 is crystallized to form a crystalline transparent conductive layer 5A. That is, a crystalline transparent conductive film 1A is obtained.

[0149] The crystalline transparent conductive film 1A is Figure 2 As shown, the transparent substrate 2, the hard coat layer 3, the optical adjustment layer 4, and the crystalline transparent conductive layer 5A are provided in this order from the bottom.

[0150] The crystalline transparent conductive layer 5A is crystalline and includes, from the bottom, a Sn region 6A, a Sn / Hf mixed region 7A, and a Hf region 8A. The element ratio and thickness of each region in the crystalline transparent conductive layer 5A are the same as those of the amorphous transparent conductive layer 5.

[0151] The surface resistance of the upper surface of the crystalline transparent conductive layer 5A is, for example, 100 Ω / □ or less, preferably 80 Ω / □ or less, and, for example, 10 Ω / □ or more.

[0152] Such a transparent conductive film 1 and a crystalline transparent conductive film 1A are included in an optical device, for example. As an optical device, for example, an image display device can be listed. When an image display device (specifically, an image display device having an image display element such as an OLED module or an LCD module) is equipped with a transparent conductive film 1 or a crystalline transparent conductive film 1A, these films (1, 1A) are patterned as needed and used as, for example, an electromagnetic wave shield, a substrate for a touch panel, etc. It is preferably used as an electromagnetic wave shield. When used as a substrate for a touch panel, as a form of the touch panel, for example, various methods such as an optical method, an ultrasonic method, an electrostatic capacitance method, and a resistive film method can be listed, which are suitable for a touch panel of an electrostatic capacitance method.

[0153] 8. Modifications

[0154] (1) Figure 1 In the embodiment shown in the figure, the transparent conductive layer 5 has a Sn / Hf mixed region 7 arranged between the Sn region 6 and the Hf region 8, but for example, Figure 3 The Sn / Hf mixed region 7 is not shown.

[0155] like Figure 3 As shown, the transparent conductive layer 5 includes a Sn region 6 and a Hf region 8 arranged on the upper surface thereof.

[0156] The transparent conductive layer 5 has an interface 9 between the lower layer and the upper layer. The interface 9 can be observed by observing the cross section of the transparent conductive layer 5 using, for example, a transmission electron microscope (TEM) or a scanning electron microscope (SEM).

[0157] (2) Figure 1In the illustrated embodiment, the Sn region 6 does not substantially have a concentration gradient of the Sn element in the thickness direction, but although not illustrated, the Sn region 6 may also have a concentration gradient of Sn in the thickness direction. In the Sn region 6, the Sn concentration at the upper end may be lower or higher than the Sn concentration at the lower end. Preferably, the Sn concentration at the upper end is lower than the Sn concentration at the lower end.

[0158] For example, such an embodiment can be obtained by sequentially forming the Sn region 6 using two or more targets having different Sn content ratios when forming the Sn region 6 by sputtering.

[0159] (3) Figure 1 In the embodiment shown, the transparent conductive film 1 includes a transparent substrate 2, a hard coating layer 3, an optical adjustment layer 4, and a transparent conductive layer 5. For example, although not shown, one or both of the hard coating layer 3 and the optical adjustment layer 4 may not be included. From the viewpoint of scratch resistance, optical properties, etc., preferably, Figure 1 The embodiment shown.

[0160] Although not shown in the figure, the transparent conductive film 1 may further include one or two or more other functional layers such as an anti-blocking layer on the lower surface of the transparent substrate 2 .

[0161] (4) About Figure 2 The crystalline transparent conductive film 1A shown can have the same configuration as the above-mentioned (1) to (3).

[0162] <Second and third embodiments>

[0163] Reference Figure 4-5 , an embodiment of the second to third embodiments of the transparent conductive film of the present invention is described. In the second to third embodiments, the same components and processes as those in the first embodiment are marked with the same reference symbols, and their detailed descriptions are omitted. In addition, the second embodiment also exerts the same effects as those in the first embodiment. Furthermore, the modified examples of the first embodiment can also be appropriately applied to the second to third embodiments.

[0164] like Figure 4 As shown, the transparent conductive film 1 of the second embodiment includes, from the bottom, a transparent substrate 2, a hard coating layer 3, an optical adjustment layer 4, and a transparent conductive layer 5, and the transparent conductive layer 5 includes: an Hf region 8 and a Sn region 6 disposed on the upper side thereof. Preferably, the transparent conductive layer 5 includes, from the bottom side, the Hf region 8, the Sn / Hf mixed region 7, and the Sn region 6.

[0165] The transparent conductive film 1 of the second embodiment is crystallized by heating to obtain a crystalline transparent conductive film of the second embodiment. Figure 2 As shown in the figure, the crystalline transparent conductive layer 5A includes the Hf region 8A, the Sn / Hf mixed region 7A, and the Sn region 6A in this order from the bottom.

[0166] like Figure 5 As shown, the transparent conductive film 1 of the third embodiment includes, from the bottom, a transparent substrate 2, a hard coating layer 3, an optical adjustment layer 4, and a transparent conductive layer 5, and the transparent conductive layer 5 includes: an Hf region 8, a Sn region 6 arranged on the upper side thereof, and an Hf region 8 arranged on the upper side of the Sn region 6. Preferably, the transparent conductive layer 5 includes, from the bottom side, the Hf region 8, the Sn / Hf mixed region 7, the Sn region 6, the Sn / Hf mixed region 7, and the Hf region 8.

[0167] The transparent conductive film 1 of the third embodiment is crystallized by heating to obtain a crystalline transparent conductive film of the third embodiment. Figure 2 As shown, the crystalline transparent conductive layer 5A includes the Hf region 8A, the Sn / Hf mixed region 7A, the Sn region 6A, the Sn / Hf mixed region 7A, and the Hf region 8A in this order from the bottom.

[0168] [Example]

[0169] Embodiment and comparative example are shown below, and the present invention is further specifically described.It should be noted that the present invention is not subject to any limitation of embodiment and comparative example.In addition, the specific numerical values ​​such as the blending ratio (containing ratio), physical property value, parameter used in the following record can be replaced by the upper limit value (defined as "below", "lower than") or the lower limit value (defined as "above", "exceeding") of the blending ratio (containing ratio), physical property value, parameter etc. recorded in the above-mentioned "specific embodiments", corresponding to them.

[0170] Example 1

[0171] As a transparent substrate, a cycloolefin-based film (thickness 22 μm, manufactured by Zeon Corporation, “ZEONORFilm”) was prepared.

[0172] A hard coating composition solution containing an ultraviolet curable acrylic resin was applied to the upper surface of the transparent substrate and dried, and then cured by ultraviolet irradiation, thereby forming a hard coating layer with a thickness of 1.0 μm.

[0173] Next, an optical adjustment composition solution containing an ultraviolet curable acrylic resin and zirconium oxide particles was applied to the upper surface of the hard coat layer and dried. Then, the optical adjustment composition was cured by ultraviolet irradiation. Thus, an optical adjustment layer with a thickness of 80 nm and a refractive index of 1.64 was formed.

[0174] Next, a transparent conductive layer is formed on the upper surface of the optical adjustment layer.

[0175] Specifically, the ITO sintered body (containing 90 wt% indium oxide and 10 wt% tin oxide) was sputtered by DC sputtering with the sputtering power set to 21 nm. Under vacuum conditions, 98% argon and 2% oxygen were introduced to a gas pressure of 0.4 Pa. Thus, an amorphous ITO layer was formed.

[0176] Then, on the upper surface of the ITO layer, an oxide sintered body containing In-Hf-Ta (manufactured by Tosoh Corporation, trade name "USR") was sputtered by DC sputtering with the sputtering power set to 10 nm. As for the vacuum condition, 98% argon gas and 2% oxygen gas were introduced to make the gas pressure 0.4 Pa. Thus, an amorphous oxide layer containing In-Hf-Ta was formed.

[0177] In this way, a transparent conductive film including transparent substrate / hard coat layer / optical adjustment layer / transparent conductive layer is produced.

[0178] Example 2

[0179] Except having changed the set thickness of each layer of a transparent conductive layer into the thickness described in Table 1, it carried out similarly to Example 1, and produced the transparent conductive film.

[0180] Comparative Example 1

[0181] For the transparent conductive layer, first, the set thickness was changed to 28nm, and the ITO sintered body (containing 90wt% indium oxide and 10wt% tin oxide) was sputtered to form the first ITO layer (lower layer). Next, the set thickness was changed to 3nm, and the ITO sintered body (containing 97wt% indium oxide and 3wt% tin oxide) was sputtered to form the second ITO layer (upper layer). In addition, an oxide layer containing In-Hf-Ta was not formed. Except for this, the transparent conductive film was manufactured in the same manner as in Example 1.

[0182] Comparative Examples 2 to 3

[0183] A transparent conductive film was produced in the same manner as in Comparative Example 1 except that the set thickness of each layer of the transparent conductive layer was changed to the thickness described in Table 1.

[0184] Comparative Example 4

[0185] The transparent conductive layer was adjusted to a set thickness of 26 nm, and an oxide layer containing In-Hf-Ta was formed. In addition, an ITO layer was not formed. Except for this, the same operation as in Example 1 was carried out to produce a transparent conductive film.

[0186] (Measurement of Film Thickness of Transparent Conductive Layer)

[0187] The thickness of each transparent conductive layer was measured by observing the cross section of each transparent conductive film of each Example and Comparative Example using a transmission electron microscope (TEM).

[0188] (Measurement of Element Ratio of Transparent Conductive Layer)

[0189] The transparent conductive film of each embodiment and comparative example was subjected to surface element analysis by X-ray photoelectron spectroscopy (ESC A). Specifically, the transparent conductive layer was subjected to qualitative analysis by wide scanning. Then, each element of In, Hf, O, and C was subjected to depth analysis based on Ar ion etching to calculate their atomic concentrations (atomic%). The measurement conditions are as follows.

[0190] Device: ULVAC-PHI, "Quantum 2000"

[0191] X-ray source: monochromatized AlKα

[0192] X-ray settings: (15kV, 25W)

[0193] Photoelectron extraction angle: 45 degrees

[0194] Neutralization conditions: Combination of neutralization electron gun and Ar ion gun (neutralization mode)

[0195] Accelerating voltage of Ar ion gun: 1kV

[0196] Grid size of Ar ion gun: 2mm×2mm

[0197] Etching rate of Ar ion gun: about 2nm / min in terms of SiO2

[0198] The diagram in Example 1 at this time is shown in Figure 6 .according to Figure 6 It is clear that the transparent conductive layer of Example 1 has a Hf region, a Sn / Hf mixed region, and a Sn region formed in sequence from the upper surface to the lower surface.

[0199] (Measurement of electrical conductivity)

[0200] The transparent conductive film of each example and each comparative example was heated at 100° C. for 60 minutes to completely crystallize the film, thereby obtaining a crystalline transparent conductive film. The surface resistivity and resistivity of the crystalline transparent conductive layer of the crystalline transparent conductive film were measured by a 4-terminal method at a 15 mm interval. The results are shown in Table 1.

[0201] (Determination of crystallization rate)

[0202] The transparent conductive films of each example and each comparative example were heated at 100° C. for a predetermined time (15 minutes, 30 minutes, and 60 minutes), and the crystallization rate at each time was measured. The results are shown in FIG. Figure 7 .

[0203] The crystallization rate was calculated by the following formula.

[0204] Crystallization rate (%) = (Rs-Ri) / (Rf-Ri)×100

[0205] Rs represents the surface resistivity (Ω / □) immediately after heating at each time, Ri represents the surface resistivity (Ω / □) before heating, and Rf represents the surface resistivity (Ω / □) after complete crystallization.

[0206] [Table 1]

[0207] [Table 1]

[0208]

[0209] It should be noted that the above invention is provided as an exemplary embodiment of the present invention, but this is merely an example and is not to be construed as limiting. Modifications of the present invention that are obvious to those skilled in the art are included in the above claims.

Claims

1. A transparent conductive film, characterized in that: The invention comprises: a transparent substrate and a transparent conductive layer arranged on one side in the thickness direction of the transparent substrate, The transparent conductive layer is amorphous. The thickness of the transparent conductive layer is greater than or equal to 10 nm and less than or equal to 35 nm. The transparent conductive layer is heated at 100° C. for 30 minutes, and the crystallization rate calculated by the following formula is 60% or more. The transparent conductive layer has, in the thickness direction, an Hf region formed of an indium oxide containing hafnium and tantalum, and an Sn region formed of an indium oxide containing tin. The thickness of the Hf region is thicker than the thickness of the Sn region, Crystallization rate (%) = (R 30min -R i ) / (R f -R i )×100 R 30min : Surface resistivity after heating at 100℃ for 30 minutes, in Ω / □, R i : Surface resistivity before heating, unit is Ω / □, R f : Surface resistivity after complete crystallization, unit is Ω / □.

2. The transparent conductive film according to claim 1, characterized in that: The Hf region is arranged on one side in the thickness direction of the Sn region.

3. The transparent conductive film according to claim 1 or 2, characterized in that: The transparent substrate is a cycloolefin film.

4. A crystalline transparent conductive film, characterized in that: The transparent conductive film is obtained by crystallizing the transparent conductive layer of the transparent conductive film according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Conductive metal oxide sintered body and its use

    JP1998269843A

  • Transparent conductive film and touch panel including the same

    JP2017062609A

  • Oxide sintered body and oxide transparent conductive film

    JP2017149636A

  • Metal oxide transparent conductive film and method of manufacturing the same

    JP2018188677A

  • Transparent conductive film

    CN105005405A